Fluorescent Carbon Quantum Dots Functionalized by Poly L-Lysine: Efficient Material for Antibacterial, Bioimaging and Antiangiogenesis Applications - Vibhute, Anuja; Nille, Omkar; Kolekar, Govind; Rohiwal, Sonali; Patil, Shubham; Lee, Seunghyun; Tiwari, Arpita Pandey (Journal of fluorescence, 2022)
This study illustrates the synthesis of functionalized carbon quantum dots (CQDs) by the one-pot pyrolysis method. The functionalization agent used in CQD synthesis was poly l- lysine (PLL). Various physicochemical techniques were employed to confirm the successful formation of PLLCQD including High resolution transmission electron microscopy (HR-TEM), UV-Vis spectroscopy, fluorescence spectroscopy; Atomic force microscopy (AFM), X-ray Photoelectron Spectroscopy (XPS) and X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy. The size of PLLCQD was confirmed by HRTEM and AFM. The synthesized PLLCQD shows bright blue fluorescence and has a quantum yield of 19.35%. The highest emission band was observed at 471nm when excited to 370nm. The prepared PLLCQD exhibited excellent antibacterial activity against Escherichia coli and Staphylococcus aureus with inhibition zone 7-20 mm. The concentrations of 0.9 to 0.1gmL-1 were studied to determine minimum inhibitory concentration (MIC) by the agar well diffusion assay method. MIC of 0.2gml -1 concentration of PLLCQD is achieved. The anti-angiogenic activity of PLLCQD was determined using (Chick Chorioallantoic Membrane) CAM assay. CAM assay is a reliable in -vivo model to study angiogenesis also; many stimulators and inhibitors have been examined by this method. This study proves higher antibacterial efficiency of PLLCQD over non functionalized CQD. PLLCQD was successfully employed in bio-imaging of the bacterial cell through fluorescence microscopy. Further, PLLCQD displayed cytotoxic effect on endothelial cells and inhibited blood vessel formation in the CAM model.
Keywords: lysin; Poly l lysine; Lysine; Carbon quantum dots; Escherichia coli; Antiangiogenesis; antibakteriální látky; Polylysine; polylysin; Carbon; spektroskopie infračervená s Fourierovou transformací; Anti-Bacterial Agents; Endothelial Cells; Antibacterial activity; Spectroscopy, Fourier Transform Infrared; endoteliální buňky; Quantum Dots; uhlík; kvantové tečky; Bioimaging